The Boyfriend - McFadden, Freida (Naperville, Illinois : Poisoned Pen Press, 2024)
Sydney Shaw, like every single woman in NYC, has terrible luck with dating until she meets the utterly perfect, charming, handsome doctor Tom, but when a woman is brutally murdered and the suspect is a mystery man who dates his victims before he kills them, Sydney can$1 (Bt shake her own horrifying suspicions.s
Includes reading group guide (pages 360-361)
Keywords: Dating (Social customs) -- Fiction; Murder -- Investigation -- Fiction; Man-woman relationships -- Fiction; Interpersonal relations -- Fiction; New York (N.Y.) -- Fiction; Romance fiction; Thrillers (Fiction)